EVALUASI KINERJA PELAKSANAAN URAIAN TUGAS PEJABAT STRUKTURAL ESELON IV PADA DINAS PERHUBUNGAN KABUPATEN KUTAI KARTANEGARA - muhammad - Subandi (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2017)
This study uses qualitative research methods, data collection techniques with interviews, the research subjects were structural official echelon IV District Department of Transportation Kukar by using purposive sampling. Based on the results obtained information that the work undertaken by all Structural Echelon IV Kutai District Department of Transportation is in conformity with the description of each task. In the implementation of the tasks of the entire Structural Echelon IV Kutai District Department of Transportation no overlap occurs between the work of structural official echelon IV. All job descriptions of all Echelon IV Structural Kutai District Department of Transportation has been implemented in accordance with their respective job descriptions.In general constraints/critical problems faced in the implementation of structural official job description Echelon IV Department of Transportation Regency, namely: job description that was too much and needed simplification to make it more clear. To help solve the problems faced by the Structural Echelon IV, therefore, based on these results, the authors suggest that to Mr. Head to immediately coordinate Secretary, the entire head of the whole Head of Sub Division and the entire Section Chief to evaluate the job descriptions each to be held in order to simplify further revision of job descriptions too much.Keywords: Evaluation, Job Description